Pengaruh Beban Pajak, Non Debt Tax Shield Terhadap Struktur Modal Pada Perusahaan Tekstil dan Garmen - Ramadhan, Rizki; Sara, Fahmi; Rosnidar (Jurnal Inovasi Akuntansi (JIA), 2025)
This study aims to examine the influence of tax burden and non-debt tax shield on the capital structure of Textile and Garment companies listed on the IDX for the period 2020-2022. Capital structure is an important aspect of corporate financial management, and understanding the factors that influence it can help companies make optimal financing decisions. The research method used is a quantitative approach with multiple regression analysis. The population of this study consists of textile and garment companies listed on the Indonesia Stock Exchange. The data tested is secondary data obtained from the company's annual financial statements for the period 2020-2022 using the SPSS version 25 test. The research results show that the tax burden has no significant effect on the capital structure, whereas the non-debt tax shield has a significant effect on the capital structure.